Antiviral use is associated with a decrease in the rate of influenza-related complications, health care resource utilization, and costs. (1st January 2021) - Wallick, Chris; Wu, Ning; To, Tu My; Keebler, Daniel; Moawad, Dalia
Abstract: Aims: To determine the effect of antiviral agents on influenza-related complications, health care resource utilization (HRU), and costs over three influenza seasons (2014–2016). Methods: This retrospective cohort study used claims data from the U.S. MarketScan Research Databases. Patients with a diagnosis code for influenza during the 2014–2016 seasons in an outpatient setting, with continuous enrollment from 1 year before to 91 d after diagnosis, were included. Patients who received an antiviral within 48 h of diagnosis were identified and propensity score–matched to a comparator cohort of untreated patients on baseline demographics, comorbid conditions, and HRU. Outcomes were assessed at days 30 and 90 after diagnosis and included respiratory-related complications (all respiratory-related and selected respiratory-related conditions [influenza, asthma, chronic obstructive pulmonary disease, or infection]), HRU, and costs. Results: Treated and matched untreated cohorts each consisted of 362, 818 patients. HRU was significantly lower in the treated cohort compared with the untreated cohort at 30 and 90 d after diagnosis, respectively (hospitalizations: 0.6% vs. 0.8% and 1.2% vs. 1.6%; emergency department [ED] visits: 4.1% vs. 4.9% and 7.9% vs. 9.2%; intensive care unit/critical care unit (ICU/CCU) admissions: 0.2% vs. 0.4% and 0.4% vs. 0.6%). Respiratory-related HRU was lower in the treated cohort at both 30 and 90 d after diagnosis ( p < .0001 for both periods). Mean all-cause total costs (including prescription costs) were significantly reduced in the treated group (day 30: 633 vs. 778; day 90: 1778 vs. 2119), despite higher prescription costs in the treated group. Limitations: The study was retrospective and subject to residual selection bias, despite propensity score matching. Additionally, despite its potential relevance to influenza severity, vaccination status was not available in our data. Conclusions: Antiviral influenza treatment is associated with a significant reduction in complications, HRU, and costs at 30 and 90 d after diagnosis.